Strategies for improvement in marketing planning: A case study in the company PDCM - de Lima, Francisca Daura; de Araújo, Joyceane Mendonça; Pereira, Rosangela da Silva; Colares, Cintya Barreiro; Fonseca, Marcello Pires (Seven Editora, 2024)
This article aims to present proposals for the optimization of the strategic marketing planning process in the PDCM company, adopting methods for a better development of the marketing strategy in the organization. Strategic marketing planning is a process of controllable and uncontrollable variables that affect the exchange relationships between companies. Modern organizations participate in constant technological changes and evolutions, in the growth and segmentation of markets, and therefore need strategies to beat competitors by reinforcing their links with their respective markets and establishing a link between the company and its consumers. Factors considered relevant for the elaboration of the article were the historical context of strategy and planning, conceptual aspects related to the subject and research based on lines of thought of renowned authors in the area, resulting in the structuring of a roadmap for the step-by-step development of an objective and easy-to-implement strategic plan. DOI:https://doi.org/10.56238/sevened2024.026-035